Qingzhen from the perspective of the other : consumption and muslim boundary-making in republican China, 1920–1949 - Faizah Zakaria (2021)
Studies of halāl (permissible) food production and consumption have often been linked to the assimilation of Muslim communities into the fabric of secular and/or non-Muslim nation-states. Much of the academic discourse on this subject has centered on the boundaries that religious dietary requirements create between an in-group of faithful adherents to the religion and an out-group of those who do not belong. Republican China (1920–1949), with its significant population of Hui and Uyghur Muslims largely concentrated in the northwestern and southeastern parts of the country, offers a new window onto this picture of socialization through commensality. The present article flips the ethnographic lens from viewing Muslim communities alone to viewing the historical perspective of outsiders who interacted and broke bread with Muslims in the Republican period, thus bringing to the surface heretofore overlooked factors that impacted the process of Muslim social boundary-making through consumption. This approach contributes to the historiography and anthropology of Islam in China by spotlighting discretionary agency and by moving away from a focus on practices of exclusivity on the part of Muslim populations or strategies of coercive repression on the part of the nation-state. This has become especially important since the rise of Communism in China, for fasting is one of the rituals of overt religiosity that the communist state has been keen to suppress. From a comparative perspective, this article also demonstrates that gender, class asymmetries, and politics may be as crucial as religion in explaining the dining strategies of Muslim minority communities.